Analisa Yuridis Kewenangan Badan Anggaran Dewan Perwakilan Rakyat Daerah Dalam Penyusunan Anggaran Pendapatan Dan Belanja Daerah Di Kabupaten Bojonegoro - Sirot, Hidayatus; Daim, Nuryanto A.; Aji, Rihantoro Bayu (Law and Humanity, 2024)
In line with the concept of regional autonomy, that autonomous regions have the authority to exercise discretion, manage and explore the potential of their natural wealth as well as human resources so that the aims and objectives of regional autonomy can be carried out properly. The management and utilization of natural resources must be carried out wisely where the results are in addition to regional financial income, and are solely for the benefit of the wider community. Therefore, how the budget function of the Regional People's Representative Council to be effective and appropriate in the preparation of APBD planning must be optimized for the benefit of the community, because often the implementation of the budget function is not carried out properly and even tends to invite problems in the future, as well as members of the Regional People's Representative Council. often trapped in the interests of groups and party interests, thus neglecting the interests of the community which should be prioritized. In order to optimize the potential of the existing budget in the region, an active role is needed from the Budget Board of the Bojonegoro Regency Regional House of Representatives. This study aims to discuss and analyze the concept of the function of the budget according to the laws and regulations and the authority of the budget agency of the Regional People's Representative Council in the context of preparing the Regional Revenue and Expenditure Budget. The type of research used in this research is normative juridical with a statutory approach and a historical approach, and ends with a qualitative descriptive analysis in producing a precise and accurate analysis.